Water quality assessment of the creek system in the University of the Philippines Academic Oval - Diaz, Abigail Myrra M.; Diola, Ma. Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The University of the Philippines Academic Oval creek system is one of several creek networks in the campus. UP as an academic institution must comply with the laws concerning water quality. Temperature, pH, total dissolved solids (TDS), turbidity, dissolved oxygen (DO), Phosphate as Phosphorus (PO4^3-P), Nitrate as Nitrogen (N03-N), chemical oxygen demand (COD) and colifoml levels were the water parameters selected to be tested for the assessment of the water quality in the Academic Oval creek system. Sampling was performed during the dry season in the Philippines, representing a worst-case scenario. Results show that DO, PO4^3-P, N03-N and coliform levels fail to comply with the Philippine surface water quality standard for Class C waters (DAO 34). Possible sources of pollution were identified based on the location of the pipes draining into the creek system. High concentrations of nutrient pollutants are observed in the stations where wastewaters are discharged. Untreated effluents discharged into the UP Academic Oval creek system affects the quality degradation of the creek waters. lmprovements on the drainage and sewerage system in the University must be employed to minimize the creek water pollution. Development programs and continuation of projects like the phytoremediation designed for the low flows in the Academic Oval should be applied to improve the state of water quality in the site area. Water quality in the creek system could be improved to achieve compliance for legitimate recreational uses.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Water quality biological assessment